Idham Chalid and Normal Islam Educational Reform in Amuntai South Kalimantan - Malisi, M Ali Sibram (Jurnal Pendidikan Islam, 2018)
This article focused on the efforts of Kiai Haji Dr. Idham Khalid as a leader in the Pesantren Normal Islam Amuntai South Kalimantan. He leads the pesantren in the context that the society needs of renewal efforts of Islamic educational aspects in the midst of the country's struggle for independence. This research is important because the Islamic boarding school (pesantren) Rasyidiyah Khalidiyah Amuntai South Kalimantan until today remains to maintain its tradition and at the same time developing it with normal Islam conception to perpetuate it as one madrasah under the largest Pesantren in South Kalimantan. This study used literature and interview as methods. The paper finds that the role of Kiai Haji Dr. Idham Chalid in educational reform at boarding schools occurs by changing its dynamics through proposed and evolutive forms. The forms are conservative at the initial phase; reformative in the middle of his leadership and transformative in the period of Pesantren Rasyidiyah Khalidiyah. These findings are based on a number of aspects of education being examined, they are the aspect of the pesantren education goals by analyzing the dynamics of the curriculum, and the flexible aspect by examining its persistency in maintaining classical books of Islam. The latter is to maintain the tradition of moderate clerics in the reproduction of Madrasah (schooling) by integrating classical books and the modern literature. Organizational survival strategy was developed by diversifying the variants of boarding school institutions which is influenced by Kyai’s leadership using a synergy and collaboration approach to prepare with cadre for organizational sustainability.